Elmo's world. Families, mail, & bath time. - Sesame Workshop (New York,NY : Sesame Workshop : manufactured by Sony Wonder, 2004)
Elmo has adventures learning about family, where the mail comes from, and bathtime.
Voice: Kevin Clash as Elmo.
Preschool.
DVD; NTSC, region 1.
Closed-captioned.
Keywords: Elmo (Fictitious character : Henson) -- Juvenile films; Families -- Juvenile films; Postal service -- Juvenile films; Baths -- Juvenile films; Puppet television programs; Children's television programs